2013
DOI: 10.1007/s12070-013-0678-y
|View full text |Cite
|
Sign up to set email alerts
|

Sinonasal Anatomical Variations: Their Relationship with Chronic Rhinosinusitis and Effect on the Severity of Disease—A Computerized Tomography Assisted Anatomical and Clinical Study

Abstract: The anatomy of the sinonasal area has a very wide rage of anatomical variations. The significance of these anatomical variations in pathogenesis of rhinosinusitis, which is the commonest disease in the region, is still unclear. The aims of the study were to compare the rate of sinonasal anatomical variations with development and severity of chronic rhinosinusitis patients. CT scan of paranasal sinuses images of 99 individuals were retrospectively reviewed. 65 cases of chronic rhinosinusitis (study group) who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
66
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 16 publications
9
66
0
5
Order By: Relevance
“…Other studies have found wide variation (2-83%) in occurrence of agger nasi. [4][5][6]8 Studies demonstrate that their major dimensions are correlated with frontal sinus diseases and lacrimation. 7 All the subjects in the study had discharge in the frontal sinus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have found wide variation (2-83%) in occurrence of agger nasi. [4][5][6]8 Studies demonstrate that their major dimensions are correlated with frontal sinus diseases and lacrimation. 7 All the subjects in the study had discharge in the frontal sinus.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Although sinusitis is a clinically diagnosed condition, imaging studies are used to assess the disease and demonstrate the sinonasal anatomy. 4 CT scan and nasal endoscopy are preferred diagnostic modalities to determine the mucosal abnormalities and bony anatomic variations of paranasal sinus and assess the possible pathogenicity of these findings in patients undergoing evaluation for sinusitis. therapy need surgical clearance of infected sinuses and establishment of ventilation and drainage.…”
Section: Introductionmentioning
confidence: 99%
“…The size of the cell may compensate the frontal recess and also the anterior part of middle meatus (5) . Kaygusuz et al (6) reported a prevalence of 61% in their study but without a significant etiology in frontal sinusitis. In our study the prevalence was 37%.…”
Section: Discussionmentioning
confidence: 71%
“…1 The anatomy of paranasal sinuses is very complicated. 2 Evaluation of the location, extent of sino nasal diseases by radiologic evaluation of the paranasal sinuses is essential in planning surgical intervention. Plain radiography, computed tomography and magnetic resonance imaging are applied in evaluating the sinuses.…”
Section: Introductionmentioning
confidence: 99%
“…3 Sinonasal region that possess frequently anatomic variations, plays an important role in the pathogenesis of paranasal sinus diseases. 2 Earlier studies have demonstrated the very high rate of anatomical variations in the sinonasal area especially the osteomeatal complexa small area located in the region between the middle turbinate and lateral nasal wall in the middle meatus representing the area of drainage of anterior ethmoid, maxillary and frontal sinuses and the importance of careful assessment of CT scan in patients with chronic rhinosinusitis, especially in the pre-operative planning prior to endoscopic surgery. [4][5][6][7] Meticulous radiographic delineation of the small structures in this region, coupled with endoscopic evaluation, provides detailed preoperative information regarding morphology and pathology.…”
Section: Introductionmentioning
confidence: 99%